2015
DOI: 10.4028/www.scientific.net/amm.808.40
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Current at Metal Cutting Process: A Literature Review

Abstract: Processing metallic materials by cutting using good electricity conductor cutting edges it appears an electrical current due mainly to the temperature in the cutting zone. Analyzing of the electrical current the information about the unfolding mode of the cutting process can be obtained. The cutting electrical current can be used in several applications: the estimation of the temperature in the cutting zone, the estimation of the cutting forces, the identification of the wear state of the cutting edge etc. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Due to the experiments, the next conclusions can be drawn: -The appearance of the electrical current at cutting is known since 1950 [2], but it's utilization in practical applications was recently developed; -The electrical current at cutting is an innovative method for the quality appreciation of the drills edges and it can be easily used; -From the analyzed drills batch, 23.33% are quality I, 43.33% quality II and 33.34% quality III; in this situation the drills batch has a satisfying quality; DOI: 10.1051/ , -If the drills are analyzed only at microscope it can be made an error in the appreciation of the drill batch quality of 14%; -The electrical current at cutting is sensible to any imperfection of the drill edge; -The electrical current at cutting has shown an improper roughness obtained at sharpening due to coarse-grain of the used abrasive wheel; -If the life of the drills from each quality group is determined, than it can be made an analysis of the quality/price ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the experiments, the next conclusions can be drawn: -The appearance of the electrical current at cutting is known since 1950 [2], but it's utilization in practical applications was recently developed; -The electrical current at cutting is an innovative method for the quality appreciation of the drills edges and it can be easily used; -From the analyzed drills batch, 23.33% are quality I, 43.33% quality II and 33.34% quality III; in this situation the drills batch has a satisfying quality; DOI: 10.1051/ , -If the drills are analyzed only at microscope it can be made an error in the appreciation of the drill batch quality of 14%; -The electrical current at cutting is sensible to any imperfection of the drill edge; -The electrical current at cutting has shown an improper roughness obtained at sharpening due to coarse-grain of the used abrasive wheel; -If the life of the drills from each quality group is determined, than it can be made an analysis of the quality/price ratio.…”
Section: Discussionmentioning
confidence: 99%
“…it appears an electrical current as consequence of the next physical effects and phenomenon: the Seebeck effect, the Thomson effect, the phenomenon of emission in metals [1][2][3][4][5][6][7][8][9][10]. Because these physical effects and phenomenon are generally based on the heat generation in the cutting process, and the wear of the cutting tool clearly depends on it, results that the measurement of the electrical current at cutting leads to a good appreciation of the cutting tool wear state.…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturing companies of cutting tools (ex. [5]) extend the use of mechanical fixed cutting inserts to the construction of tool systems. There are no exceptions to the roughing reamers which are frequently used cutting tools.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [1][2][3][4][5][6][7][8] showed that it exists a direct dependency between the voltage of the electrical current at cutting and the temperature in the cutting zone: the higher the temperature is, the higher the voltage of the electrical current is.…”
Section: Introductionmentioning
confidence: 99%